2013
DOI: 10.1093/carcin/bgt124
|View full text |Cite
|
Sign up to set email alerts
|

The chemopreventive activity of the butyric acid prodrug tributyrin in experimental rat hepatocarcinogenesis is associated with p53 acetylation and activation of the p53 apoptotic signaling pathway

Abstract: The reversibility of non-genotoxic phenotypic alterations has been explored in order to develop novel preventive and therapeutic approaches for cancer control. Previously, it has been demonstrated that histone deacetylase (HDAC) inhibitor tributyrin, a butyric acid prodrug, to have chemopreventive effects on rat hepatocarcinogenesis. The goal of this study was to determine molecular mechanisms associated with the chemopreventive activity of tributyrin. Male Wistar rats were allocated randomly to untreated cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
0
26
0
5
Order By: Relevance
“…The polyphenol quercetin may prevent cardiovascular disease due to its anti-oxidative stress; the healthy male subjects consumed 150 mg/d quercetin for 8 wks intermitted by a three-week washout phase (Pfeuffer, 2013). The cancer chemopreventive experiment on the Wistar rat hepatocarcinogenesis model treated with histone deacetylase inhibitor, tributyrin (butyric prodrug, 2g/kg body wt) daily for 8 wks resulted in lower HDAC activity and Hdac3 and Hdac4 gene expression, and etc (de Corti, 2013). Moreover, Steliou k et al indicate that the histone deacetylase inhibitor butyrate is not only capable to suppress cancer growth, but also to regulate other medical disorders, such as neurological, DOI:http://dx.doi.org/10.7314/APJCP.2014.15.11.4539 Aberrant Epigenetic Alteration in Eca9706 Cells withNanoliposomal Quercetin and Butyrate -Role of Epigenetic-NF-κB hematological and insulin resistant obesity in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol quercetin may prevent cardiovascular disease due to its anti-oxidative stress; the healthy male subjects consumed 150 mg/d quercetin for 8 wks intermitted by a three-week washout phase (Pfeuffer, 2013). The cancer chemopreventive experiment on the Wistar rat hepatocarcinogenesis model treated with histone deacetylase inhibitor, tributyrin (butyric prodrug, 2g/kg body wt) daily for 8 wks resulted in lower HDAC activity and Hdac3 and Hdac4 gene expression, and etc (de Corti, 2013). Moreover, Steliou k et al indicate that the histone deacetylase inhibitor butyrate is not only capable to suppress cancer growth, but also to regulate other medical disorders, such as neurological, DOI:http://dx.doi.org/10.7314/APJCP.2014.15.11.4539 Aberrant Epigenetic Alteration in Eca9706 Cells withNanoliposomal Quercetin and Butyrate -Role of Epigenetic-NF-κB hematological and insulin resistant obesity in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Tributyrin shares p21WAF1 as a common gene target for de-repression in cancer cells 41 . Similar to butyrate, tributyrin has also been shown to acetylate p53 42 , and valproic acid has been shown to acetylate Ku70 in medulloblastoma cells 43 . More recently, it was reported that the ketone body d-β-hydroxybutyrate (βOHB) (IC 50 : 2~5mM) is an endogenous and specific inhibitor of class I HDACs.…”
Section: 0 Protein Acetylation and Dietary Chemopreventive Agentsmentioning
confidence: 98%
“…These doses of folic acid and tributyrin were two times lower from those used in previous studies. [9][10][11][12] Rats (n 5 7) in control group were subjected to the "resistant hepatocyte" model of carcinogenesis only ( Fig. 1).…”
Section: Animals and Experimental Designmentioning
confidence: 99%